High salt compatible oxyanion receptors by dual ion imprinting. Issue 16 (14th April 2020) - Shinde, Sudhirkumar; Mansour, Mona; Incel, Anil; Mavliutova, Liliia; Wierzbicka, Celina; Sellergren, Börje
Abstract : Imprinting of an ion-pair in presence of mutually compatible anion and cation host monomers leads to polymers showing enhanced ion uptake in competitive high ionic strength buffers. Abstract : The design of hosts for either cations or anions is complicated due to the competition for binding by the host or guest counterions. Imprinting relying on self-assembly offers the possibility to stabilize the guest and its counterion in a favorable geometry. We here report on a comprehensive supramolecular approach to anion receptor design relying on concurrent recognition of both anion and cation. This was achieved by high order complex imprinting of the disodium salt of phenyl-phosphonic acid in combination with neutral urea and sodium ion selective 18-crown-6 monomers. The polymers displayed enhanced affinity for the template or inorganic phosphate or sulfate in competitive aqueous buffers, with affinity and selectivity increasing with increasing ionic strength. The presence of engineered sites for both ionic species dramatically increases the salt uptake in strongly competitive media such as brine.